Quality, satisfaction and perceived value in users of sports services in Mexico - Reyes Robles, Marina; Ceballos Gurrola, Oswaldo; Medina Rodríguez, Rosa Elena; Rojo Villa, Jesús Alfredo; López Esquerra, Luis Ernesto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of the study was to evaluate the quality, satisfaction and perceived value of users of sports services and facilities according to gender, age and educational level, as well as to establish predictive models of perceived quality, perceived value and satisfaction. A total of 481 users participated, 58% of whom were men and 42% women, with a mean age of 17.73 ± 5.40. The EPOD2 instrument was used, consisting of perceived quality (20 items), satisfaction (4 items) and perceived value with one item. The highest rated factors of perceived quality were the staff 4.17 ± .87 and trainer 3.92 ± 1.13, and the lowest rated factor was the facilities 3.18 ± 1.26. Satisfaction and perceived value also received positive ratings. There were significant differences according to gender, age and educational level. Finally, a significant relationship was found between perceived quality and perceived value, as well as between perceived value and satisfaction.